2012
DOI: 10.1017/s0024282912000370
|View full text |Cite
|
Sign up to set email alerts
|

Bryoria rigida, a new Asian lichen species from the Himalayan region

Abstract: Molecular studies have revealed the presence of yet another species in the Bryoria bicolor complex in China, which confirms that the mountains of SE Asia to be an evolutionary centre for Bryoria sect. Divaricatae. The new species B. rigida is formally described. It is characterized by a stiff and coarse thallus, which contains fumarprotocetraric acid and often protocetraric acid as the main substances. A key to the divaricate species of Bryoria in the Himalayan region is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Brodo & Hawksworth (1977) suggested that Divaricatae is an evolutionary ancient group but recent molecular phylogenies (Myllys et al 2016;Wang et al 2017) including this study (Fig. 3) show that this section is of recent origin and is currently undergoing diversification, especially in South-East Asia but also in western North America (Jørgensen et al 2012;Myllys et al 2016;Wang et al 2017;McCune et al 2020). High speciation rates have previously been reported in several Parmeliaceae taxa, including Bryoria section Implexae (Boluda et al 2019) and Usnea (Kraichak et al 2015;Mark et al 2016).…”
Section: Phylogeny Of Bryoriamentioning
confidence: 61%
See 3 more Smart Citations
“…Brodo & Hawksworth (1977) suggested that Divaricatae is an evolutionary ancient group but recent molecular phylogenies (Myllys et al 2016;Wang et al 2017) including this study (Fig. 3) show that this section is of recent origin and is currently undergoing diversification, especially in South-East Asia but also in western North America (Jørgensen et al 2012;Myllys et al 2016;Wang et al 2017;McCune et al 2020). High speciation rates have previously been reported in several Parmeliaceae taxa, including Bryoria section Implexae (Boluda et al 2019) and Usnea (Kraichak et al 2015;Mark et al 2016).…”
Section: Phylogeny Of Bryoriamentioning
confidence: 61%
“…In contrast to these findings, recent molecular studies in Bryoria have also revealed the existence of previously unknown lineages, resulting in the recognition of several new species based on single to three-locus phylogenies but also supported by chemistry and morphology (Jørgensen et al 2012; Boluda et al 2015; Myllys et al 2016; Wang et al 2017). The new species appear to have restricted distribution areas and are confined mainly to South-East Asia and/or western North America.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been comprehensively studied in North America and northern Europe (Brodo & Hawksworth 1977; Myllys et al 2011 a ); however, morphological simplicity and chemical variability make its taxonomy difficult, and recent molecular data have resulted in several changes (Velmala et al 2009, 2014; Myllys et al 2014). Recent studies have discovered additional new species in Bryoria from east-central Asia (Myllys et al 2011 b ; Jørgensen et al 2012), southern South America and the Antarctic (Olech & Bystrek 2004; Fryday & Øvstedal 2012). Temperate South America is a region with an unexpectedly low reported Bryoria diversity, suggesting that additional species may be awaiting discovery in the region.…”
Section: Introductionmentioning
confidence: 99%